2015
DOI: 10.1111/jnp.12079
|View full text |Cite
|
Sign up to set email alerts
|

Subtle visuomotor difficulties in preclinical Alzheimer's disease

Abstract: The VMC task is able to discriminate Pre-AD from CTR individuals. Moreover, VMC results are associated with AB42 levels in CN individuals, suggesting that visuomotor dysfunction may be a sensitive marker of Pre-AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Further, in a recent study of older adults with preclinical AD (defined by having elevated CSF Aβ indicative of AD, but with unimpaired cognition) Mollica et al (2019) found that the speed and variability (a measure of rhythm) of simple finger tapping tests on a computer keyboard are abnormal in preclinical AD, and the degree of variability correlates with CSF Aβ levels [ 19 ]. These findings support earlier studies that determined hand reaction times correlate highly with CSF Aβ biomarker levels in preclinical AD [ 20 ] and progressively worsen over the AD continuum [ 20 22 ]. Additionally, it has been shown that even with unimpaired cognition ApoE4 carriers have been found to have delayed hand reactions compared to non-carriers, suggesting hand movements deteriorate at the very earliest stages of preclinical AD [ 20 ].…”
Section: Introductionsupporting
confidence: 91%
“…Further, in a recent study of older adults with preclinical AD (defined by having elevated CSF Aβ indicative of AD, but with unimpaired cognition) Mollica et al (2019) found that the speed and variability (a measure of rhythm) of simple finger tapping tests on a computer keyboard are abnormal in preclinical AD, and the degree of variability correlates with CSF Aβ levels [ 19 ]. These findings support earlier studies that determined hand reaction times correlate highly with CSF Aβ biomarker levels in preclinical AD [ 20 ] and progressively worsen over the AD continuum [ 20 22 ]. Additionally, it has been shown that even with unimpaired cognition ApoE4 carriers have been found to have delayed hand reactions compared to non-carriers, suggesting hand movements deteriorate at the very earliest stages of preclinical AD [ 20 ].…”
Section: Introductionsupporting
confidence: 91%
“…Hippocampal volume was smaller in SCD+ than SCD− when using both the CCI and Worry and approached significance for the ECog + Worry definition. Such decreased hippocampal volume is consistent with other SCD studies that included worry ( Scheef et al, 2012 ), and memory clinic consultation ( Kim et al, 2013 , Mollica et al, 2017 ). However, we did not find hippocampal volume group differences when defining SCD+ with the ECog.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it was expected that, overall, results would exhibit agreement; however there were considerable differences between values obtained on the MCS-A and MCS-B. Some studies have found the informant´s perception of the elderly subject with SCI to be a more reliable predictor of cognitive impairment than the elderly subject´s report 11 , 36 - 38. The SCI, when not associated with objective memory alteration, may reflect a distorted awareness of the current cognitive state compared to the past.…”
Section: Discussionmentioning
confidence: 99%